PSYCHOLOGICAL STATUS OF READYNESS FOR DISTANCE AND ONLINE STUDY OF PEDAGOGICAL WORKERS IN CONDITIONS OF FORMAL AND NON-FORMAL EDUCATION - Shven, Yaroslava Leonidivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The psychological state of readiness of pedagogical workers for distance and online learning in the conditions of continuous education – the system of formal and non–formal education is investigated; the survey data are analyzed in order to psychologically and pedagogically optimize the effectiveness of learning in adult education.